Anthropology in the Anthropocene an earthed theory for our extended present - Antweiler, Christoph 1956- (Springer, 2024)
Chapter 1. Humans Make Earth History – New Earth and New Anthropology -- Chapter 2. Cultural Resonance – Loss of Orientation, Fears, and Hope -- Chapter 3. End-Time Stories – Mostly Dramatic Framings -- Chapter 4. Critique – Strengths and Weaknesses of Anthropocene Thinking -- Chapter 5. Anthropocene Anthropology – Contributions and Opportunities -- Chapter 6. Conditio Humana – the Geologization of Culture.-Chapter 7. Human Niche Construction – Building Blocks for Synthesis -- Conclusion.
Includes bibliographical references and index
The original submitted manuscript has been translated into English. The translation was done using artificial intelligence. A subsequent revision was performed by the author(s) to further refine the work and to ensure that the translation is appropriate concerning content and scientific correctness.
Keywords: Klimaänderung; Anthropologie; Historische Geologie; Anthropozän; Human ecology.; Environmental education.; Philosophical anthropology.; Environment.